Biosecurity Implementation and Detection of Infectious Myo Necrosis Virus in Penaeus monodon Seed at Hatchery Surya Prima Benur - Zainal Usman; Siti Aisyah Saridu; Ihwan Ihwan; Supryady Supryady; Ardana Kurniaji; Fanggi Fanggi (Berkala Perikanan Terubuk, 2022)
Diseases control in tiger shrimp farming activities needs to be done by applying biosecurity and early detection of IMNV. This study aimed to identify the application of biosecurity and IMNV detection in tiger shrimp hatchery activities at the Hatchery Surya Prima Benur. The method of collecting data on the application of biosecurity at the Surya Prima Benur Hatchery is carried out by observing field activities, interviews and participating in activities directly. IMNV detection in tiger prawn fry was carried out by PCR machine. The results of the study indicated that the application of biosecurity at the research site includes infrastructure biosecurity, personnel biosecurity, biota biosecurity, and environmental biosecurity. Detection of IMNV in 6 samples of fry showed negative IMNV results indicated by the absence of a band on the 139 bp molecule according to the positive control. The results of this study can be used as technical guidelines for the implementation of biosecurity and the IMNV inspection process in tiger shrimp hatchery activities.